PENINGKATAN KEMAMPUAN NUMERASI MENGGUNAKAN MEDIA ULAR TANGGA DI KELAS II SDN KOLAM KIRI KECAMATAN WANARAYA KABUPATEN BARITO KUALA - Rahmayanti, Herlina; Cahyani, Irni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low numeracy skills of second-grade students at SDN Kolam Kiri due to the limited use of engaging learning media in mathematics instruction. The study aimed to improve students' numeracy skills through the implementation of the Snakes and Ladders learning media. This research employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, implementation, observation, and reflection. Data were collected through learning achievement tests, observations of student and teacher activities, and documentation. The results showed a significant improvement in students' numeracy skills. Learning mastery increased from 25% in the pre-cycle to 60% in Cycle I and reached 86.6% in Cycle II. Student activity improved from 51.4% to 97.2%, while teacher activity increased from 64.58% to 95.8%. These findings indicate that the Snakes and Ladders learning media effectively improves numeracy skills, student participation, and the quality of mathematics learning. Therefore, this media can be used as an innovative learning alternative for lower elementary school students.